The Association Between Skipping Breakfast and Anxiety and Depression in Adolescents—A Scoping Review - Tatiana Naumoska; Kristina Zafirovski; Fahad Hanna (Children)
Background: Anxiety and depression are among the most common mental health disorders affecting adolescents worldwide. Skipping breakfast is a prevalent dietary behaviour linked to inadequate nutrient intake, which may contribute to the development or exacerbation of mental health issues in this age group. Despite growing interest, a comprehensive synthesis of evidence on the association between breakfast omission and adolescent anxiety or depression remains limited. Objectives: This scoping review aimed to synthesise existing research on the association between skipping breakfast and the risk of anxiety and/or depression in adolescents. Methods: A systematic scoping review was conducted using the Joanna Briggs Institute (JBI) methodological framework. A comprehensive search of PubMed, ProQuest, and EBSCOhost databases was performed, focusing on studies published in English between 2014 and 2024. Keywords included “skipping breakfast,” “risk,” “anxiety,” “depression,” and “adolescen*.” Studies were screened and selected based on predefined inclusion and exclusion criteria. Results: Out of 1671 initially identified studies, 12 met the inclusion criteria. The majority were cross-sectional (n = 9), with one prospective cohort study, one secondary data analysis, and one systematic review with meta-analysis. Most studies reported a significant association between breakfast skipping and increased risk of anxiety and depression in adolescents. Only one study reported no significant relationship between the two variables. Conclusions: This review underscores a consistent association between skipping breakfast and elevated risk of anxiety and depression among adolescents. While causality remains to be established, breakfast omission emerges as a modifiable lifestyle factor with potential public health implications. These findings highlight the need for prospective research, as well as the importance of community- and school-based health promotion strategies that advocate for regular and nutritious breakfast consumption as part of broader mental health support efforts.